HEAT FLUX MEASUREMENT WITH SONIC ANEMOMETER AND COMPARISON WITH PARAMETERIZATION - FAUZAN SUTISNA (12809036); Pembimbing : Dr. Tri Wahyu Hadi, MUHAMMAD
This research aims to determine the temporal variation of the heat flux, its comparison with the observed heat flux and determine the ratio of heat flux in the bulk parameterization with observations from Bawean Island. Sonic anemometer observations conducted from July 22 to August 8, 2013 at five different points. Analysis was performed on these observational data to see patterns of heat flux and its comparison with the heat flux observed at Cabauw, Netherlands. Estimated heat flux is calculated by using the bulk parameterization then compared with the results of observation. Observational data for each location shows diurnal variation, so it can be said that Bawean Island has homogeneous data. Comparative analysis of the heat flux at Cabauw, the Netherlands showed a range of different heat flux values due to differences in the intensity of solar radiation received. The difference in the intensity of solar radiation caused by the position of the sun at different subtropical regions with tropical regions. Comparison of heat flux to the bulk estimation results indicate that less good results even show a diurnal pattern. Diurnal pattern that occurs due to the mixing layer that estimates using horizontal wind speed is considered equal at any altitude. After doing the analysis, it is concluded that the Bawean Island homogeneous with diurnal variation pattern, heat flux observed at Cabauw, Netherlands and heat flux from bulk estimation results do not represent heat flux in Bawean Island.